A Double-Blind Placebo-Controlled Crossover Study of the Effect of Beetroot Juice Containing Dietary Nitrate on Aortic and Brachial Blood Pressure Over 24 h - Kukadia, Suraj; Dehbi, Hakim-Moulay; Tillin, Therese; Coady, Emma; Chaturvedi, Nish; Hughes, Alun D. (Frontiers in Physiology, 2019)
Dietary inorganic nitrate in beetroot can act as a source of nitric oxide and has been reported to lower brachial blood pressure (BP). This study examined the effect of inorganic nitrate in beetroot juice on aortic (central) BP acutely and over the subsequent 24-hour period. A double blind, randomised, placebo-controlled crossover trial was performed in fifteen healthy, normotensive men and women (age 22 to 40 y). Participants were randomised to receive beetroot juice containing nitrate (6.5 7.3 mmol) or placebo beetroot juice from which nitrate had been removed (<0.06 mmol nitrate). Effects on aortic systolic BP were measured at 30 minutes (primary endpoint), 60 minutes and over a subsequent 24h period using an ambulatory BP monitor. Carotid-femoral pulse wave velocity (cfPWV) was also measured at 30 minutes. Following a washout period, the procedure was repeated within seven days with crossover to the opposite arm of the trial. Compared with placebo, ingestion of beetroot juice containing nitrate lowered aortic systolic BP at 30 minutes by 5.2 (1.9 to 8.5) mmHg (mean (95% confidence interval); p < 0.01). A smaller effect on aortic systolic BP was observed at 60 minutes. There were minimal effects on brachial BP or cfPWV. Effects on aortic systolic BP were not sustained over the subsequent 24 hours and there were no effects on other hemodynamic parameters during ambulatory monitoring. A single dose of beetroot juice containing nitrate lowers aortic BP more effectively than brachial BP in the short term, but the effects are comparatively short-lived and do not persist over the course of the same day